2018
DOI: 10.3390/ijms19113413
|View full text |Cite
|
Sign up to set email alerts
|

Use of Yarrowia lipolytica Lipase Immobilized in Cell Debris for the Production of Lipolyzed Milk Fat (LMF)

Abstract: Lipase immobilized on Yarrowia lipolytica cell debris after sonication of yeast cells (LipImDebri) was used in hydrolysis reaction as a novel strategy to produce lipolyzed milk fat (LMF). Extracellular (4732.1 U/L), intracellular (130.0 U/g), and cell debris (181.0 U/g) lipases were obtained in a 4 L bioreactor using residual frying oil as inducer in 24 h fermentation process. LipImDebri showed a good operational stability retaining 70% of lipolytic activity after the second cycle and 40% after the fourth. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…After centrifugation (4 • C, 4600× g, for 5 min), the sonicated biomass (cell debris with lipase) was resuspended in 200 mM MOPS buffer pH 7.0 and frozen for subsequent measurement of enzyme activity. This sonicated biomass with high lipase activity [16,17] was used as a catalyst. It was resuspended in MOPS buffer, let adhere to solid surfaces (polystyrene and PET), as described in Section 2.4.2, and used as an immobilized biocatalyst.…”
Section: Production Of Cells With Enzymatic Activity (Cell Debris)mentioning
confidence: 99%
See 4 more Smart Citations
“…After centrifugation (4 • C, 4600× g, for 5 min), the sonicated biomass (cell debris with lipase) was resuspended in 200 mM MOPS buffer pH 7.0 and frozen for subsequent measurement of enzyme activity. This sonicated biomass with high lipase activity [16,17] was used as a catalyst. It was resuspended in MOPS buffer, let adhere to solid surfaces (polystyrene and PET), as described in Section 2.4.2, and used as an immobilized biocatalyst.…”
Section: Production Of Cells With Enzymatic Activity (Cell Debris)mentioning
confidence: 99%
“…Although it has been reported that Y. lipolytica cells present lipase enzymatic activity [15], a higher lipase activity is detected when the cells are treated with ultrasound, which results in cell debris associated with lipase [17]. Y. lipolytica cell debris were tested for lipase activity (hydrolysis of p-nitrophenyl laurate into p-nitrophenol), and a positive result was obtained, as depicted in Table 5 (before adhesion).…”
Section: Application Of Cells Immobilized On Polymer Surfacesmentioning
confidence: 99%
See 3 more Smart Citations